Pelaksanaan Standard Operational Prosedur Protokol Kesehatan di Bagian Kantor Depan Padma Hotel Bandung - Yayan Sugiarto; Dewi Riski Yanti (Akademi Pariwisata NHI Bandung, 2021)
This study aims to determine the implementation of service standard operational procedures at the Front Office of Padma Hotel Bandung when dealing with covid 19. The collection method used is a quantitative method. Data collection techniques are carried out by distributing questionnaires, observation. while the data analysis technique using a Likert scale. The results of the initial research implementation that the service at the front office of the hotel is mainly seen from the implementation of standard operating procedures in the application of health protocols has only reached 70%, Padma Hotel has determined that the implementation of this SOP must be carried out 100%. Problems in the research: how, consistency, efficiency, error methods, problem solving and SOP work maps that are run at the front office of Padma Hotel Bandung. The results of the study 1) consistency is in the Enough category, 2) Efficiency in the implementation of SOPs is in the Less category, 3) Minimize errors is in the Less category, 4) SOP problem solving is in the Less category and the Work Map on SOP Implementation is in the Enough category.